SOME CHALLENGES IN CROSS-CULTURAL COMPARATIVE RESEARCH - Krouglov, Alex (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The paper examines the application of qualitative methods in comparative research in a recent international project Industrial Relations in Multilingual Environments at Work (IR MultiLing) which explored how the use of languages other than a dominant language may affect labour relations in various work situations in Europe. The novelty of the current research covered in this paper lies in the fact that it investigates some challenges in developing the best ways of creating an analytical framework when conducting cross-cultural research involving multinational teams of researchers from France, Germany, Hungary, Italy, Spain and the United Kingdom. It also analyses approaches in completing an effective comparison of the contexts and findings across various cultures. Although, there are many examples of qualitative research in literature, this paper aims at exploring some credible approaches in conducting cross-cultural research by international teams of scholars at several key stages: desk research and contextualisation, identifying clear parameters for fieldwork, systematising and comparing findings of the research. The purpose of this research is to provide guidance and some tools to researchers engaged in cross-cultural comparative research using qualitative methods.